COMPETING GRAMMARS OF WORLD ORDER: CHINA’S FOUR GLOBAL INITIATIVES AND THE NEW U.S. NATIONAL SECURITY STRATEGY IN MIRROR PERSPECTIVE - Monica Gheorghita, (PEOPLE: International Journal of Social Sciences, 2026)
This article examines the transformation of contemporary world order through a comparative analysis of China’s four global initiatives—the Global Development Initiative, Global Security Initiative, Global Civilization Initiative, and Global Governance Initiative—and the United States National Security Strategy of December 2025. The purpose of the research is to move beyond conventional power-transition or rivalry frameworks and to assess how these documents articulate competing conceptions of international legitimacy, authority, and governance in a post-hegemonic global context. The article asks how each set of documents defines the sources of order, the role of institutions, and the acceptable instruments of power, and what their interaction reveals about the nature of the emerging world order. Methodologically, the article adopts a qualitative, interpretive analysis combining close textual reading with comparative and mirror-based conceptual analysis. The documents are treated not as sectoral policy statements, but as order-defining texts that encode broader normative and institutional visions. The findings demonstrate that China’s four initiatives constitute a coherent ordering doctrine grounded in performance-based legitimacy, development-first sequencing, inclusive security, civilizational pluralism, and reformed multilateralism. By contrast, the NSS 2025 articulates a sovereignty-centered, transactional, and leverage-driven conception of order, in which legitimacy is re-nationalized, institutions are endorsed conditionally, and economic and security instruments are instrumentalized in an open manner. Read in mirror perspective, these projects do not simply compete for influence; they advance structurally different grammars of world order that often operate at cross-purposes. The article concludes that the interaction between these two ordering projects contributes to the emergence of a plural and negotiated world order, characterized less by hegemonic replacement than by legitimacy fragmentation. Global governance is increasingly shaped by overlapping and contested justificatory regimes, in which authority must be continuously negotiated rather than assumed.